2022
DOI: 10.1111/lang.12525
|View full text |Cite
|
Sign up to set email alerts
|

Syntax Matters: Exploring the Effect of Linguistic Similarity in Third Language Acquisition

Abstract: Over the last two decades, the question of to which linguistic cues learners pay attention when they decode a new language has been subject to controversy in the field of third language (L3) acquisition. In this article, we present an artificial language learning experiment that investigated how lexical and syntactic similarities between an artificial L3 and preexisting grammars impact crosslinguistic influence at the very beginning of the acquisition process. We exposed four groups of 30 Norwegian-English bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…At the same time, the results of the Follow-up task, where structural and lexical similarity were aligned in the artificial language, indicate that both structural and lexical similarity may play a significant role as predictors of relative activation of individual representations and are important contributing factors in additional language acquisition. This resonates with recent findings in Jensen and Westergaard (2022), showing that both lexical and syntactic cues in the input play a role for CLI in early L3 acquisition. Our Russian participants who were exposed to a novel artificial language that was both lexically and structurally like Russian performed at ceiling on all conditions, were able to inhibit the subject-first bias, and follow the case cue in conditions where the case cue and word order were in a mismatch.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, the results of the Follow-up task, where structural and lexical similarity were aligned in the artificial language, indicate that both structural and lexical similarity may play a significant role as predictors of relative activation of individual representations and are important contributing factors in additional language acquisition. This resonates with recent findings in Jensen and Westergaard (2022), showing that both lexical and syntactic cues in the input play a role for CLI in early L3 acquisition. Our Russian participants who were exposed to a novel artificial language that was both lexically and structurally like Russian performed at ceiling on all conditions, were able to inhibit the subject-first bias, and follow the case cue in conditions where the case cue and word order were in a mismatch.…”
Section: Discussionsupporting
confidence: 91%
“…It is nevertheless noteworthy that no trace of V2 transfer was detected, especially as instructions were given in Norwegian, which could potentially have primed participants with that language (cf. Jensen and Westergaard 2022). Even though speakers were slightly more accurate in their judgments of the RC items than the MC items (the condition in which L1-transfer could potentially manifest), the paired t-tests showed that there was no significant difference between participants' sensitivity for MC and RC items in either the timed or the untimed experiment.…”
Section: Discussionmentioning
confidence: 87%
“…It is widely recognized that cross-linguistic influence is one of the most important resources available to the L3 learner (e.g., Witney & Dewaele, 2018), especially when the target language and previously learnt languages reveal similarities (e.g., Schepens et al, 2016;Jensen & Westergaard, 2023). For example, it has been shown that the larger the linguistic distance between L3 and L2, the lower the degree of L3 acquirability (Schepens et al, 2016).…”
Section: Facilitative Effects Of Multilingualism On Additional Langua...mentioning
confidence: 99%